Applied Aspects Of Some Agrya Dravya - Naik, Padma Lochan; Kotecha, Mita; Nathani, Sumit; Yadav, Shweta (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda is not only a life science but also a spiritual science that deals with how to maintain a healthy life and to prevent the onset of diseases. Brihatrayee comprises of three textbooks i.e. Charaka Samhita, Sushruta Samhita and Ashtanga Hridaya. these texts books are excellent in describing different diseases and their treatment by using Ahara Dravya and Aushadha Dravya. In Agrya Prakarana both Ahara Varga Dravya and Aushadha Varga Dravya have been explained to get an approach towards nutritional and medicinal values.